Sexual consent - Popova, Milena (The MIT press essential knowledge series, 2019)
Introduction -- Consent 101 -- Negotiating consent -- Sex and power : between yes and no -- Culture and consent -- Consent knowledges, consent activisms -- #MeToo : now what? -- Glossary -- Notes -- Further reading -- Index.